Reconstructing History from the Grave Yards of Ethiopia’s Past: The Case of Tigray - Ferede, Wuhibegezer; Haile, Gezae (Ethiopian Journal of Social Sciences, 2018)
his research aimed at locating, identifying and documenting graveyards and funeral rites for reconstructing the life history and achievements of prominent personalities in Ethiopia’s past and theier social philosophy of death as depicted in grave markers and oral discourses of the society in the Regional State of Tigray. Accordingly, data was collected through in-depth informant interview about funeral rituals and rites, field observation for deciphering information from grave markers, and document analysis for reviewing historical records such as eyewitness accounts. The data was collected from Churches and Monasteries in Mekelle, Tembien, Adwa, Aksum, Maychewu and their environs. Hence, this paper traverses as far as the fourth century to examine the Christianization process in Ethiopia based on Abba Selama Kesate Berhane’s  grave markswhich is found at Enda Abba Selama in Tembien. It also examined the achievement and lives of St. Frumentius, Abune Yohanis, Abba Merha Christos, Christopher Dagma, Bashai Awallom and Rass Alula, and traced the missing link in their historical biographic narratives. The social philosophy about death, funeral rituals and manifestation of grief were also analyzed from oral narratives and inference from practices. The critical examination of the collected data provided baseline information about the lives of unknown but historically important personalities such as Christopher Dagma, son of Vasco Dagma, who came to Ethiopia leading the Portuguese soldiers in the war against Gragn. It also shed light on some controversial issues such as the periodization of the Christianization of Ethiopia and Ethio-Eritrea relations.. Furthermore, the study attested that the funeral rituals and the bio-data carved on physical setting of the cemeteries and inscriptions(symbols) had immense dataset about family line, demographic and social pattern, biographies, social status, causes and the society’s  view of death in the study area. As these graveyards are deteriorating and disappearing very fast, the study emphasizes the urgent need for the deployment of a multidisciplinary research team  in order to digitize, document and rescue the vanishing dataset in these sites.